(untitled) (Editora Impacto Científico, 2025)
Introduction: Obstructive sleep apnea (OSA) is associated with significant cardiovascular complications. Electrocardiography (ECG) and 24-hour Holter monitoring may reflect OSA-related changes and serve as screening tools. Objective: To critically review the main electrocardiographic and Holter alterations in patients with OSA. Methods: Narrative review of articles published between 2015 and 2025 in PubMed, Scopus, and SciELO, including observational studies, clinical trials, and reviews. Results: OSA is associated with atrial fibrillation, conduction disturbances, QTc prolongation, P-wave abnormalities, and Holter-detected arrhythmias (pauses, atrioventricular blocks, extrasystoles). CPAP therapy reduces AF recurrence and improves autonomic parameters. Conclusion: ECG and Holter are accessible tools for OSA screening, but polysomnography remains indispensable. Robust clinical trials are needed to confirm impact on major outcomes. DOI: https://doi.org/10.56238/edimpacto2025.091-006